Gen Z's Path to Brand Loyalty in Photo Studios: The Influence of Brand Experience, Community, and Engagement - Djong Surya Atmandra; Kurnadi Gularso (Riviera Publishing, 2024)
The photography industry, particularly photo studios, is undergoing a significant transformation due to the development of digital technology and social media. Generation Z, as a digital generation, interacts with photography in unique ways, making brand community, brand experience and customer engagement increasingly relevant for building strong relationships with photo studios. This study aims to determine and analyze Generation Z's loyalty to photo studios, focusing on the mediating role of customer participation behavior and customer citizenship behavior. This study uses a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationship between latent variables. Data was collected through questionnaires distributed to Generation Z consumers in Indonesia. The findings show that brand experience and customer engagement significantly increase customer participation and citizenship behavior, which in turn strengthen customer loyalty. However, brand community does not directly influence citizenship behavior or customer loyalty, highlighting the need for a comprehensive approach in building customer loyalty. These results have important implications for photo studios, indicating that creating positive brand experiences and increasing customer engagement are critical to fostering customer loyalty, especially among Generation Z. Photo studios should focus on improving these areas to build a stronger and more loyal customer base.